Mega-projects and sustainability in Durban, South Africa: Convergent or divergent agendas?. (January 2015) - Hannan, Sylvia; Sutherland, Catherine
Abstract: This paper explores the relationship between urban regeneration and sustainability within the post-apartheid city of Durban, South Africa, using mega-projects as a lens. In the past 20 years Durban has been shaped by both globalisation and post-apartheid restructuring, through processes of pro-growth urban regeneration and social transformation. Simultaneously, sustainability has emerged as a critical concept in the development and management of the city. This paper examines the regeneration landscape of the city, focussing on the implementation of two "new" mega-projects, as a regeneration strategy. These are the Moses Mabhida Stadium and the Point Waterfront Development. Furthermore it reflects upon the inclusion of sustainable city principles within the development of these projects, in order to determine the extent to which this urban regeneration strategy considers sustainability. The paper concludes that the two agendas of urban regeneration and sustainability are currently divergent rather than convergent, and suggests that they require further integration to ensure a more sustainable urban future.